Acer Truncatum Seed Oil Alleviates Learning and Memory Impairments of Aging Mice - Li, Xiao; Li, Ting; Hong, Xiao Yue; Liu, Jian Jun; Yang, Xi Fei; Liu, Gong Ping (Frontiers in Cell and Developmental Biology, 2021)
Aging, characterized by a time-dependent functional decline of physiological integrity, is the major independent risk factor for many neurodegeneration diseases. Therefore, it’s necessary to look for natural food supplements to extend the healthy lifespan of aging people. We here treated normal aging mice with acer truncatum seed oil, and found that the seed oil significantly improved the learning and memory ability. Proteomics revealed that the seed oil administration changed many proteins expression involving in biological processes, including complement and coagulation cascades, inflammatory response pathway and innate immune response. BDNF/TrkB signaling pathway was also activated by acer truncatum seed oil treatment. And the seed oil administration increased the expression of postsynaptic related proteins including PSD95, GluA1 and NMDAR1, and decreased the mRNA level of inflammatory factors containing IL-1β, TNF-α and IL-6. These findings suggest that acer truncatum seed oil holds a promise as a therapeutic food supplement for delaying aging with multiple mechanisms.